SAMPLING OF THE PLAN OF REPAIRS OF THE MAIN EQUIPMENT IN THE ELECTRICAL POWER SYSTEM - O. I. Alexandrov (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The main aspects of creation of the formal-and-functional mathematical models supporting a system for prompt resolution of repair requires in a complex electric power system are considered in the article. In accordance with the standards of repairs, inspections, replacement of elements of the main equipment or devices of a system of automation, inclusion of spare capacity, various switches, as well as with the frequency of outages adopted in practice, the decisionmaking process is formalized and automated as the problem of scheduling optimal daily schedules of blackouts, functioning as a part of automated system of dispatching management of electric power system. The main problems that hinder mathematical modeling of decision-making concerning operational applications for the repair of the main power equipment of power system are: the need for a coherent account of a large number of limiting factors and indicators of effectiveness of the solutions; the need of information and algorithmic trade-offs with the objectives of adjacent levels of spatial, temporal and functional hierarchy; the lack of developments in the standardization of information structures that adequately reflect the process of finding solutions; the computational complexity of several restrictions of the optimization problem subject to mandatory registration.